2000
DOI: 10.1007/pl00013936
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of ITS Nuclear rDNA Sequence Data and AFLP Markers for Phylogenetic Studies in Phyllostachys (Bambusoideae, Poaceae)

Abstract: Two contrasting molecular techniques, namely DNA sequences and amplified fragment length polymorphisms (AFLP) were used to investigate phylogenetic relationships of Phyllostachys, a large, economically important genus of woody bamboos. DNA sequences of the internal transcribed spacer (ITS) region of nuclear ribosomal DNA (nrDNA) were used in a parsimony analysis. PhyrrOStachys was well supported as monophyletic with Chimonobambusa as its closest allied genus. The 5s spacer region of nrDNA was investigated but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 29 publications
3
57
0
2
Order By: Relevance
“…AFLP fingerprints are highly reproducible and generally produce a large number of polymorphic markers (Becker et al, 1995;Ridout and Donini, 1999;Hodkinson et al, 2000). We have demonstrated that they can be applied to the study of genetic variation in poppies.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…AFLP fingerprints are highly reproducible and generally produce a large number of polymorphic markers (Becker et al, 1995;Ridout and Donini, 1999;Hodkinson et al, 2000). We have demonstrated that they can be applied to the study of genetic variation in poppies.…”
Section: Discussionmentioning
confidence: 91%
“…AFLP fingerprinting is based on the selective amplification of restriction fragments from a digest of genomic DNA. The resulting complex fingerprints are reproducible and provide a wide number of informative markers derived from the many loci dispersed throughout the genome (Ridout and Donini, 1999 Hodkinson et al, 2000). AFLP has been used to detect genetic variation in highly inbred lines of cereal crops and for the study of clonal variation in plants (Mackill et al, 1996;Paul et al, 1997;Waugh et al, 1997;Hodkinson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that AFLPs be the method of choice for phylogenetic studies of closely related organisms when other characters (e.g. morphological characters) are identical [3,16]. An advantage of the AFLP procedure is the fact that the whole genome is used as the source of information for the banding patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, the power of this region fails to resolve the phylogenetic assessments (Després et al, 2003). AFLP emerges as an efficient technique to solve difficulties whereas cpDNA is not sufficient to identify phylogenies, particularly among closely related species or at the intraspecific level (Hodkinson et al, 2000;Koopman et al, 2001;Xu and Sun, 2001;Zhang et al, 2001;Karakaş et al, 2013). AFLP analysis can detect high levels of polymorphism and has high repeatability and speed of analysis.…”
Section: Introductionmentioning
confidence: 99%